Preparation and properties of PLA/PHBV/PBAT blends 3D printing filament. (6th March 2019) - Yang, Mengru; Hu, Jing; Xiong, Na; Xu, Bo; Weng, Yunxuan; Liu, Yanhui
Abstract: The PLA/PHBV/PBAT blends with varied ratio were extruded into filaments by a 3D consumables extruder and the dumbbell-shaped specimens were prepared by a desktop 3D printer. The properties of composites and printed samples were characterized by x-ray diffraction (XRD), differential scanning calorimetry (DSC), melt flow index (MFI), scanning electron microscope (SEM) and tensile strength test. The process parameters of 3D printing were also surveyed. Compared with injection molded specimens with identical composition, the PLA crystallinity of printed specimens was greatly improved; SEM micrographs of the 3D printed specimens fracture surface showed a more uniform microstructure distribution with smaller oval cavities structure; and the 3D printed specimens exhibited superior tensile strength and elongation at break. This study may expand the application fields of PLA based 3D printing filaments.